ChemInform Abstract: New Alkaloids from Aconitum vaginatum. Issue 46 (18th November 2014) - Li, Juan; Chang, Hang; Zhao, Wenyu; Pi, Huifang; Ruan, Hanli; Zhang, Peng
Abstract isolation and structure elucidation of two new amide alkaloids, vaginatunine A (Ia) and B (Ib), and the new C18‐diterpenoid alkaloid, vaginatunine C (II)